Drinking Patterns and Behavioral Consequences: A Cross-Sectional Study among Romanian University Students - NASUI, Bogdana Adriana (Zdr Varst, 2015)
BACKGROUND: Alcohol/binge drinking among university students has become a major public health problem. Many of young students will be exposed to substantial changes in living arrangements, socialization groups and social activities during the transitional period. AIM: The aim of this study was to analyse the alcohol consumption in Romanian university students, and to describe the behaviours occurring after drinking. METHODS: A cross-sectional study was conducted on 468 undergraduate students, from a university for medicine and law. Of these students, 35.5% were males and 64.5% were females. The mean age of students was 21.9 ± 3.22 years. Validated anonymous paper questionnaires were completed voluntary by the students. Questionnaires contained demographic items, six questions for determining the level of alcohol consumed in terms of quantity and frequency, and 19 statements or problems resulting from drinking. RESULTS: The findings of the study showed that males drunk more units of alcohol/week than females (p<0.001). The prevalence of abstainers was 10.8% in males and 17.6% in women. Heavy drinkers (drinking 5 or more drinks more than once a week) were more common among male (19.3%) than among female students (16.2%). Most frequently, drinking behaviours are related to academic performance, and the possible link between poor academic performance and alcohol consumption appears tenuous and merits further investigation. CONCLUSION: Effective intervention strategies should be implemented to prevent students’ alcohol consumption and adverse health and social consequences resulting from this behaviour.